Innovation in coastal protection works using Labuan Blocks - Tan, King Seng, Ir.; Nor Hisham, Mohd. Ghazali, Ir.; Ong, Hon Lim, Ir. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/